2010
DOI: 10.1089/vbz.2009.0035
|View full text |Cite
|
Sign up to set email alerts
|

Larval Environmental Temperature and the Susceptibility ofAedes albopictusSkuse (Diptera: Culicidae) to Chikungunya Virus

Abstract: A key feature in the recent widespread epidemic of the mosquito-borne alphavirus chikungunya virus (CHIKV) was the important role of Aedes albopictus, formerly regarded as a secondary vector, compared to the presumed primary vector Aedes aegypti. Ae. albopictus, a container-inhabiting mosquito, is an invasive species that occurs over a wide geographic range spanning tropical and temperate latitudes. In this study we examine the effects of a broad range of larval rearing temperatures on CHIKV infection, dissemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
132
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(139 citation statements)
references
References 46 publications
6
132
1
Order By: Relevance
“…albopictus DENV-1 infection, although these effects do not appear to alter rates of vertical transmission, which indicate a unique reproductive barrier(s) to transmission. These results are consistent with Westbrook et al (2010), who showed that Ae. albopictus reared at a cooler larval temperature (18 C) had higher chikungunya virus infection and dissemination rates compared with those reared at a warmer larval temperature (32 C).…”
Section: Discussionsupporting
confidence: 93%
“…albopictus DENV-1 infection, although these effects do not appear to alter rates of vertical transmission, which indicate a unique reproductive barrier(s) to transmission. These results are consistent with Westbrook et al (2010), who showed that Ae. albopictus reared at a cooler larval temperature (18 C) had higher chikungunya virus infection and dissemination rates compared with those reared at a warmer larval temperature (32 C).…”
Section: Discussionsupporting
confidence: 93%
“…Our model assumes that all parameters are independent. However, it is likely that some are correlated; for instance temperature may simultaneously influence vector competence, biting rate, and vector life history [51,52]. To our knowledge, there have been no lab or field studies examining the effects of temperature on Zika replication in mosquitoes and there is very little on the affect of temperature on chikungunya's EIP [9, 52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Sindbis virus infection and dissemination rates have been found to be higher in Ae. aegypti mosquitoes after rearing larvae at higher temperatures [80], whereas, in contrast, studies have shown increased CHIKV (and YF) infection rates in larvae raised at lower temperatures [71,72].…”
Section: The Role Of Climate In Insect Vector-pathogen Interactionsmentioning
confidence: 91%
“…aegypti [71] and Ae. albopictus [72]. Dengue virus (DENV) infection rates are also temperature-dependent, demonstrating increased infection and transmission rates at higher temperatures [73][74][75][76], as well as altered infection rates and EIP in response to fluctuating temperatures and diurnal temperature range (DTR).…”
Section: The Role Of Climate In Insect Vector-pathogen Interactionsmentioning
confidence: 99%